How do low-status expatriates deal with crises? stress, external support and personal coping strategies during the COVID-19 pandemic - Haist, Joshua; Kurth, Philipp (Emerald, 2022)
Purpose: Low-status expatriates (LSEs), a highly vulnerable group, have been significantly affected by the ongoing COVID-19 pandemic. This study explores the stressors that continue to impact LSEs in Germany and their access to support during the pandemic. Design/methodology/approach: An interpretivist, qualitative research approach was employed. The authors utilised a multi-level data collection strategy that combined interview and questionnaire data from 16 expatriates and 16 social actors. The data were analysed using a directed content analysis method. Findings: LSEs experienced high levels of stress that were further exacerbated by the introduction of COVID-19 control measures that were intended to slow the spread of the virus. LSEs are particularly vulnerable due to their overrepresentation in precarious professions and the associated job insecurity. Critically, external support from employers and social actors is generally lacking, leaving LSEs to rely on their own personal coping strategies in difficult times. Research limitations/implications: The earlier Expatriate crisis Framework highlights the importance of external support for expatriates. However, this framework does not sufficiently account for personal coping strategies that are particularly important for individuals that cannot access such external support (e.g. LSEs). Herein, the authors offer a revised framework that is more applicable to LSEs. Practical implications: Current practices are problematic, necessitating policy changes at both governmental and organisational levels. Originality/value: This study provides unique insights into the ways in which the pandemic has affected the already precarious position of LSEs and identifies the importance of personal coping strategies in the absence of external sources of support.
Special Issue: Global Mobility in Times of Global Calamity: COVID-19 Reactions, Responses, and Ramifications for the Future of Work
Keywords: Germany; Support; Stress; COVID-19 pandemic; Hidden expatriates; Low-skilled; Low-status; Low-wage